Strategic assessment of cassava research priorities - CGIAR Research Program on Roots, Tubers and Bananas (2015)
Following its official launch in 2012, the CGIAR Research Program on Roots, Tubers and Bananas (RTB) embarked on a strategic assessment of research priorities for five of its major crops (banana, cassava, potato, sweet potato, and yams). The objective of this exercise was to determine the expected impact each research options would generate in terms of economic benefits, poverty reduction, food security, nutrition and health, gender equity, and environmental sustainability. The priority assessment was a collaborative study conducted by RTB members and partners using a common methodology across all five crops.